Perhitungan faktor utilitas baterai pesawat dengan menggunakan metode sistem dinamis untuk mengukur tingkat ketersediaan baterai - Nyimas Desy Rizkiyah; Muhamad Arya Dwi Pangga; Alfin Yumaela Lestari; Mega Purnamasari (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
The role of the aircraft maintenance industry as an aircraft maintenance service which is expected to be able to maintain the survival of the aircraft itself. For example, PT GMF Aero Asia is one of the Strategic Business Units (SBU) owned by PT Garuda Indonesia which is specialized in aircraft maintenance, repair and overhaul services which include aircraft frames, engines, components and their support. In this study, a quantitative assessment of the availability and capability of maintenance facilities was carried out using a preventive maintenance method with a dynamic system model approach that describes the level of availability and maintenance capability of aircraft batteries. Calculations have been made with a computer program, POWERSIM, in actual conditions that in December 2020 the total number of batteries in maintenance was 102 batteries for Airbus types and 80 batteries for Airbus types. With the assumption that starting in 2021 there will be an increase in the number of aircraft by 1 (one) unit per month, then at the end of the study period until July 2021 the calculation of the utility factor will be as follows, the total utility factor for Boeing is still below 1, while for Airbus starting April 2021 the utility factor is above 1. So that the operator's ability to handle Airbus type battery maintenance is not sufficient. For this purpose, an alternative scenario needs to be created, namely scenario 1 by adding one operator per shift and scenario 2 by increasing the operator's workload in handling the number of batteries handled to as many as 6 battery units. The results of the calculation of the utility factor show that in both conditions the scenario gives a value below 1. The best choice in terms of simplicity in handling the number of operators, then the choice of condition scenario 2 is the best choice.